Pengaruh Kompensasi, Motivasi, dan Disiplin Kerja terhadap Kepuasan Kerja Karyawan di PT Pelindo Balikpapan - Nurul Hikmah; Imam Arrywibowo; Marlinda Waty (CV. Ulil Albab Corp, 2026)
Employee job satisfaction has become a critical indicator of organizational effectiveness and workforce sustainability in the contemporary business environment. This study aims to analyze the influence of compensation, motivation, and work discipline on employee job satisfaction at PT Pelindo Balikpapan. The study employed a quantitative approach involving forty-three employees selected through a saturated sampling (census) technique. Data were collected through observation, interviews, and structured questionnaires using a Likert scale. Data analysis was conducted using Partial Least Squares (PLS) with the assistance of SmartPLS. The findings indicate that compensation, motivation, and work discipline each have a positive and significant effect on employee job satisfaction. Among these variables, motivation emerged as the most dominant predictor of job satisfaction. Furthermore, the coefficient of determination indicates that compensation, motivation, and work discipline collectively explain a substantial proportion of the variance in employee job satisfaction. These findings highlight the importance of strengthening motivational strategies, equitable compensation systems, and organizational discipline in enhancing employee satisfaction and overall organizational performance.